Synergistic Dynamic Conductivity and Interfacial Hydrogen Bonding in Liquid Metal Composites for Ultrastable Strain Monitoring - Jianyu Xu (459140) (2025)
Liquid metal (LM)-based flexible strain sensors face critical challenges, including LM leakage, high surface tension, and conductive network fracture under high strain, which severely limit their particle applications. To overcome these limitations, this study developed an innovative sensor by integrating a liquid metal–glass fiber (LMGF) conductive paste onto an adhesive casein gel (CG) substrate via mask printing. The GFs dynamically regulate LM migration and enable pathway reconstruction during deformation. The casein gel enhances interfacial stability through hydrogen bonding between its amino/carboxyl groups and the oxide layer on the LM surface. Remarkably, the sensor achieves the following: the resulting LMGF-CG sensor exhibits stable sensing performance up to 600% strain (with a 0.5 mm line width) and displays minimal signal drift after 500 loading cycles at 50% strain. The sensor’s sensitivity and operational range could be effectively tuned by adjusting the conductive line width and coil geometry. Furthermore, the device demonstrated conformal skin attachment for reliable monitoring of diverse physiological activities (e.g., eyebrow movement, swallowing, joint motion, and respiration), stable function in saline and PBS environments, and the ability to power stretchable LED arrays. A key sustainability feature is the full recyclability of the material via the NaOH dissolution of the interfacial oxide films. This work successfully resolves core challenges of LM sensors by synergizing dynamic GF regulation and casein-mediated adhesion, providing a versatile platform for sustainable, high-performance, flexible electronics.